Paediatric intensive care and neonatal intensive care airway management in the United Kingdom: the PIC‐NIC survey1. (15th August 2018) - Foy, K. E.; Mew, E.; Cook, T. M.; Bower, J.; Knight, P.; Dean, S.; Herneman, K.; Marden, B.; Kelly, F. E.
Summary: In 2011, the Fourth National Audit Project (NAP4) reported high rates of airway complications in adult intensive care units (ICUs), including death or brain injury, and recommended preparation for airway difficulty, immediately available difficult airway equipment and routine use of waveform capnography monitoring. More than 80% of UK adult intensive care units have subsequently changed practice. Undetected oesophageal intubation has recently been listed as a 'Never Event' in UK practice, with capnography mandated. We investigated whether the NAP4 recommendations have been embedded into paediatric and neonatal intensive care practice by conducting a telephone survey of senior medical or nursing staff in UK paediatric intensive care units (PICUs) and neonatal intensive care units (NICUs). Response rates were 100% for paediatric intensive care units and 90% for neonatal intensive care units. A difficult airway policy existed in 67% of paediatric intensive care units and in 40% of neonatal intensive care units; a pre‐intubation checklist was used in 70% of paediatric intensive care units and in 42% of neonatal intensive care units; a difficult intubation trolley was present in 96% of paediatric intensive care units and in 50% of neonatal intensive care units; a videolaryngoscope was available in 55% of paediatric intensive care units and in 29% of neonatal intensive care units; capnography was 'available' in 100% of paediatric intensive care units and in 46% of neonatal intensive care units, and 'always available' in 100% of paediatric intensive care units and in 18% of neonatal intensive care units. Death or serious harm occurring secondary to complications of airway management in the last 5 years was reported in 19% of paediatric intensive care units and in 26% of neonatal intensive care units. We conclude that major gaps in optimal airway management provision exist in UK paediatric intensive care units and especially in UK neonatal intensive care units. Wider implementation of waveform capnography is necessary to ensure compliance with the new 'Never Event' and has the potential to improve airway management.